MONITORING HAMA KUMBANG BADAK (Oryctes rhinoceros L.) PADA TANAMAN KELAPA (Cocos nucifera L.) MENGGUNAKAN FEROMON DI KECAMATAN MAPANGET KOTA MANADO - Tegar P. Prok; Robert W. Tairas; James B. Kaligis; Edy F. Lengkong (COCOS, 2019)
ABSTRACT This research aims to determine the population of O. rhinoceros with pheromones and trap devices. This research was carried out in the paniki experimental garden in Mapanget Subdistrict, Manado city, from October to December 2019. This research used a survey method which was carried out directly on coconut plants. Determination of the location of the imago O. rhinoceros sample collection was done by purposive sampling, ie taking the imago O. rhinoceros sample trapped in the pheromone trap. This study uses pheromones (ethyl 4methyloctanoate), for traps made from buckets and installed 4 sides of zinc plates at the top of the bucket, zinc plates made holes to hang pheromones, then at the bottom of the bucket is perforated. This is so that when there is rain, water will not flood the bucket. Traps used consist of traps that are yellow and colorless, traps are then placed on a coconut plantation with a distance between traps 100-150 meters and placed diagonally. Observations are made once a week for 2 months, beetles caught during observation are counted. The results showed that 83 yellow-painted traps could be trapped and unpainted traps could trap 78 individuals. Keywords: O. rhinoceros, pheromones, Coconut